ECM-binding properties of extracellular vesicles: advanced delivery strategies for therapeutic applications in bone and joint diseases - Peng Wang; Johanna F. A. Husch; Onno J. Arntz; Peter M. van der Kraan; Fons A. J. van de Loo; Jeroen J. J. P. van den Beucken (Cell Communication and Signaling)
Abstract Extracellular vesicles (EVs) and the extracellular matrix (ECM) are essential in maintaining bone and joint health by facilitating intercellular communication, regulating tissue processes and providing structural support. EVs with a large surface area carry diverse biomolecules to steer the function of cells in their surroundings. To understand how EVs localize to specific sites, we here review the available knowledge on EV surface biomolecules and their interactions with ECM components that are crucial for regulating bone remodeling, cartilage maintenance, and immune responses, playing roles in both tissue homeostasis and pathological conditions, such as arthritis and osteoporosis. More importantly, using analyses of animal experimental data, we illustrate the effect of ECM-based biomaterials (e.g. hydrogels, decellularized matrices, and ECM-mimetic scaffolds) as carriers for EVs toward effective EV delivery in regenerative and immunomodulatory therapies in bone and joint tissue. These biomaterials enable sustained release and targeted delivery of EVs, promoting bone and cartilage regeneration. The insights of this review can be utilized to advance the development of cutting-edge therapies for skeletal tissue regeneration and disease management.